2019
DOI: 10.1007/s11695-019-04154-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roux-en-Y Gastric Bypass on Osteoclast Activity and Bone Density in Morbidly Obese Patients with Type 2 Diabetes

Abstract: Introduction-Roux-en-Y gastric bypass (RYGB) is a well-established treatment for morbid obesity and type 2 diabetes. The effects of RYGB on bone metabolism and bone health are largely unknown.Objective-Determine the changes in osteoclast function and bone density 1 year after RYGB as compared with a control group undergoing a diabetes support and education program (DSE).Design-A prospective cohort study with patients matched for weight and age assigned to RYGB or DSE. Setting-Large academic institution.Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Among the 15 articles evaluating the relationship between bariatric surgery and the lumbar spine, there were 2 [ 26 , 28 ] articles in which the average age of subjects was less than 30 years; 6 [ 32 , 34 , 35 , 37 , 41 , 44 ] articles included 30- to 40-year-old patients; and 7 [ 29 , 30 , 34 , 38 , 40 , 42 , 45 ] articles included patients older than 40 years of age. The age division was not clear in one of the articles [ 47 ]; therefore, we did not include this in the subgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 15 articles evaluating the relationship between bariatric surgery and the lumbar spine, there were 2 [ 26 , 28 ] articles in which the average age of subjects was less than 30 years; 6 [ 32 , 34 , 35 , 37 , 41 , 44 ] articles included 30- to 40-year-old patients; and 7 [ 29 , 30 , 34 , 38 , 40 , 42 , 45 ] articles included patients older than 40 years of age. The age division was not clear in one of the articles [ 47 ]; therefore, we did not include this in the subgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Bariatric surgery produces detrimental effects on bone health and there is a significant and non-uniform reduction in BMD across different bone sites [3,16,41,42]. In the short-term, the preferential bone loss at FN and weight-bearing sites suggests that this could be a response to unloading after weight loss [43,44]. Only a few previous studies, mainly focusing on standard RYGB, have evaluated long-term BMD outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent trial on bone marker variation after RYGB found similar results, with increased CTX-1, P1NP and BSAP 2 years after surgery 40 . Another study addressing bariatric type 2 diabetic patients found that there was a significant 280% increase in osteoblast activity, and a significant decrease in BMD of lumbar spine (−4.0%, p<0.05) one year after RYGB 41 . Several studies to date have focused on BMD variation after RYGB, where most of them used DXA measurements and detected a prominent areal Bone Mineral Density (aBMD) decline at the proximal femur during the first year after surgery, with decreases that range from 6 and 11% 42 .…”
Section: Bariatric Surgery Techniques and Its Impact On Bonementioning
confidence: 98%